A targeted secretome profiling by multiplexed immunoassay revealed that secreted chemokine ligand 2 (MCP‐1/CCL2) affects neural differentiation in mesencephalic neural progenitor cells. Issue 4 (12th January 2015) - Colucci‐D'Amato, Luca; Cicatiello, Anna Emilia; Reccia, Mafalda Giovanna; Volpicelli, Floriana; Severino, Valeria; Russo, Rosita; Sandomenico, Annamaria; Doti, Nunzianna; D'Esposito, Vittoria; Formisano, Pietro; Chambery, Angela; Krijgsveld, Jeroen
<x xml:space="preserve">Abstract</x> Chemokines and cytokines, primarily known for their roles in the immune and inflammatory response, have also been identified as key components of the neurogenic niche where they are involved in the modulation of neural stem cell proliferation and differentiation. However, a complete understanding of the functional role played in neural differentiation and a comprehensive profiling of these secreted molecules are lacking. By exploiting the multiplexing capability of magnetic bead–based immunoassays, we have investigated the changes of the expression levels of a set of chemokines and cytokines released from the pluripotent neural cell line mes‐c‐myc A1 following its differentiation from a proliferating phenotype (A1P) toward a neural (A1D) phenotype. We found a subset of molecules exclusively released from A1P, whereas others were differentially detected in A1P and A1D conditioned media. Among them, we identified monocyte chemoattractant protein‐1/chemokine ligand 2 (MCP‐1/CCL2) as a proneurogenic factor able to affect neuronal differentiation of A1 cells as well as of neuroblasts from primary cultures and to induce the elongation and/or formation of neuritic processes. Altogether, data are suggestive of a main role played by the CCL2/CCR2 signaling pathway and in general of the network of secreted cytokines/chemokines in the differentiation of neural progenitor cells toward a neural fate.